The Effect Of Ai Utilization, Creative Content, And Product Innovation On Entrepreneurial Competitiveness Of Food And Beverage Umkm In The Digital Era In Sukolilo, Surabaya - Novitasari, Cindy; Rahmiyati, Nekky (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to examine the effect of Artificial Intelligence (AI) utilization, creative content, and product innovation on strengthening the entrepreneurial competitiveness of food and beverage MSMEs in Sukolilo, Surabaya. The main objective is to understand the contribution of each variable, both partially and simultaneously, in enhancing MSMEs’ competitiveness amid increasingly tight and digital-based business competition. The study employs a quantitative approach involving 30 MSME owners selected through purposive sampling. Data were collected using Likert-scale questionnaires specifically designed to measure the research variables. The data were then analyzed using multiple linear regression to test the relationships and impacts of the variables individually and collectively on MSME competitiveness. The findings indicate that AI utilization, creative content, and product innovation have a positive and significant influence on strengthening MSME competitiveness. AI assists business actors in operational efficiency and data-driven decision-making, creative content expands market reach and strengthens business image, while product innovation becomes the dominant factor in attracting consumer attention and creating competitive advantage. These results highlight the importance of integrating technology and creativity to support the sustainability and development of MSMEs in the digital era. Selain itu, studi ini memberikan bukti empiris bahwa transformasi digital memainkan peran penting dalam meningkatkan kinerja UMKM, khususnya di sektor makanan dan minuman. Hasil penelitian ini diharapkan dapat menjadi referensi bagi pelaku UMKM dalam merumuskan strategi bisnis dan bagi para pembuat kebijakan dalam merancang program yang mendorong adopsi teknologi dan inovasi di kalangan UMKM.